Principles and practice of constraint programming : 26th International Conference, CP 2020, Louvain-la-Neuve, Belgium, September 7–11, 2020, proceedings /: 26th International Conference, CP 2020, Louvain-la-Neuve, Belgium, September 7–11, 2020, proceedings. (2020) - Unknown
No abstract available